IMPLEMENTATION OF TOURISM DEVELOPMENT POLICY IN PANTAI INDAH PANDAN, PANDAN DISTRICT, CENTRAL TAPANULI DISTRICT: IMPLEMENTASI KEBIJAKAN PENGEMBANGAN PARIWISATA DI PANTAI INDAH PANDAN KECAMATAN PANDAN KABUPATEN TAPANULI TENGAH - Waruwu, Krisdayanti (LPPM UPMI, 2024)
Indah Pandan Beach (PIP) is located on Jl. Sisingamangaraja – Padangsidempuan. To reach this beach we can travel overland from Medan City for 9 hours by road. Initially this beach was called Bosur Beach, as its development and management changed, this beach changed its name to Indan Pandan Beach (PIP) and became a very interesting photo spot. The waves here are also not too big and tend to be safe for playing around. Visitors can do various activities such as surfing, snorkeling, renting a boat and so on.